Murder in old Bombay - March, Nev, 1967- (Minotaur Books, 2020)
"In 19th century Bombay, Captain Jim Agnihotri channels his idol, Sherlock Holmes, in Nev March's Minotaur Books/Mystery Writers of America First Crime Novel Award-winning debut. In 1892, Bombay is the center of British India. Nearby, Captain Jim Agnihotri lays in Poona military hospital recovering from a skirmish on the wild northern frontier, with little to read but newspapers. The case that catches Jim's attention is being called the crime of the century: Two women fell from the busy university's clock tower in broad daylight. Moved by the widower of one of the victims - his certainty that his wife and sister did not commit suicide - Jim approaches the Framjis and is hired by the Parsee family to investigate what happened that terrible afternoon. But in a land of divided loyalties, asking questions is dangerous. Jim's investigation disturbs the shadows that seem to follow the Framji family and triggers an ominous chain of events. Based on real events, and set against the vibrant backdrop of colonial India, Nev March's lyrical debut Murder in Old Bombay brings this tumultuous historical age to life"--